What does a study of nonsteroidal anti-inflammatory drug sales statistics give the Russian Federation? - Viktoriya Georgievna Barskova; Viktoria Georgiyevna Barskova (Современная ревматология, 2011)
The paper analyzes the data obtained by Pharmexpert on the sales of nonsteroidal anti-inflammatory drugs in the Russian Federation. Ibuprofen, ketorolac, diclofenac, and nimesulide are sales leaders. Possible reasons for the popularity of a number of medications and whether it is expedient to use intramuscular formulations are considered. The WHO data on indi-cations for and contraindications to the use of injectable dosage form are given.